Evolution and Prospects of the «Alternative for Germany» - Аlexander А. Sorokin; Yuri D. Korovin (Научно-аналитический вестник Института Европы РАН)
In recent years, the populist Alternative for Germany (AfG) party, which systematically opposes the ruling mainstream parties, has become active on the German political scene. In contrast to the approach of the mainstream parties, the AfG’s views on governance and engagement with the European Union now pose a threat to the coalition of the Social Democratic Party of Germany (SPD), the Free Democratic Party (FDP) and the Alliance 90 / The Greens because of the increasing popularity of right-wing populists among the German electorate. In autumn 2025, Germany will hold federal elections to the Bundestag, which will determine the political course of the country for the next 5 years. The purpose of this article is to assess the prospects of the Alternative for Germany party in the Bundestag elections in 2025.A significant part of the article is devoted to reviewing the ideological evolution of the party, which has gone from a minor moderate party to the leading opposition force in the country. This is essential in order to understand the implications of the current rise in social tensions and scandals around Alternative and how this may affect its future political sustainability. Authors provide a forecast of the party’s chances of success in the parliamentary elections and assess the risks that the AfG may face during the electoral struggle. The conclusion is made that the chances of the Alternative for Germany party to enter the government in 2025 will depend on its capacity to timely eliminate the accumulated internal contradictions, such as the excessive radicalisation of the party and the lack of a unified ideological component among its leaders.